2009
DOI: 10.1021/cm9010663
|View full text |Cite
|
Sign up to set email alerts
|

A General and Flexible Synthesis of Transition-Metal Polyphosphides via PCl3 Elimination

Abstract: We report a straight-forward, solvent-free moderate temperature synthetic method for the production of several phosphorus-rich transition-metal phosphides (orthorhombic FeP2, cubic CoP3, cubic NiP2, monoclinic CuP2, and monoclinic PdP2). Notably, this synthetic approach provides facile access to the high-temperature/high-pressure cubic phase of NiP2. The general synthetic strategy involves the direct reaction of anhydrous metal dichloride pressed pellets with molecular P4 vapor or solid−solid reactions between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 64 publications
2
64
0
Order By: Relevance
“…38−48 Nanocrystalline nickel phosphides are also of interest as electrodes for lithium ion batteries. 49 Several methods exist for the synthesis of nickel phosphide nanocrystals (mostly Ni 2 P and Ni 12 P 5 ), including chemical vapor deposition, 50 solution phase (colloidal) synthesis, 16,51−70 solvothermal synthesis, 71−77 electrosynthesis, 78 hydrothermal synthesis, 79 solid-state synthesis, 80 microwave synthesis, 81 and temperature-programmed phosphate reduction. 82 These methods yield nickel phosphide nanocrystals with various morphologies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…38−48 Nanocrystalline nickel phosphides are also of interest as electrodes for lithium ion batteries. 49 Several methods exist for the synthesis of nickel phosphide nanocrystals (mostly Ni 2 P and Ni 12 P 5 ), including chemical vapor deposition, 50 solution phase (colloidal) synthesis, 16,51−70 solvothermal synthesis, 71−77 electrosynthesis, 78 hydrothermal synthesis, 79 solid-state synthesis, 80 microwave synthesis, 81 and temperature-programmed phosphate reduction. 82 These methods yield nickel phosphide nanocrystals with various morphologies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The rare report of nanostructured mono-phosphorus TMPs is mainly resulted from their high nucleation energy and the lack 75 of suitable synthetic routes. 25,26 Hence, to obtain carbon coated nanostructured mono-phosphorus TMPs is highly potential to further improve their rate capability.…”
Section: Introductionmentioning
confidence: 99%
“…Due to excellent properties of Co-P compounds, the synthesis technologies have been extensively investigated [16][17][18] and the structural analysis has also been conducted in order to understand the intrinsic mechanism [19][20][21][22][23]. By the linear muffin-tin orbital method in the atomic sphere approximation (LMTO-ASA), it has been found that Co 2 P with hexagonal structure exhibits ferromagnetism while Co 2 P with orthorhombic structure reveals non-magnetic character [19].…”
Section: Introductionmentioning
confidence: 99%